Employers' skill preferences across Europe: between cognitive and non-cognitive skills - Kureková, Lucia Mýtna [Verfasser]; Beblavý, Miroslav [Verfasser]; Haita, Corina [Verfasser]; Thum, Anna-Elisabeth [Verfasser] (My University, 2016)
"This article analyses online job advertisements to identify skills that are demanded in selected low- and medium-skilled occupations. We explore data from the publicly administered cross-European EURES job search portal and quantify the different cognitive and non-cognitive skills requested by employers in small European economies. While we find that the service sector demands non-cognitive skills more than other types of occupation, the skill-mix demanded is very diverse across countries, implying that other domestic factors shape how demand is formulated. Our work shows that online portals can become a useful source for studying employers’ demand at the micro-level to inform employment, education and training policies." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.2.3.2 Anforderungen & Bedarfe; I 2.2 Europa; Arbeitsmarkt; Stellenbeschreibung; Analyse; Früherkennung; Qualifikationsanforderung; Berufsanforderung; Geringqualifizierter; Europa